The Effects of Creditor Rights and Bank Information Sharing on Borrower Behavior: Theory and Evidence - John Boyd; Hendrik Hakenes; Amanda Heitz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper provides a comprehensive theoretical and empirical analysis of “creditor rights” and “information sharing” throughout over 1.8 million private firms in Europe. We show that many of the outcomes associated with greater levels of creditor rights can be obtained with higher information sharing between banks. Both theory and empirics show that creditor rights and information sharing are associated with greater firm leverage, lower profitability, and greater distance to default. Moreover, theory and empirics find that creditor rights and information sharing are robust substitutes. Our analysis suggests that poor creditor rights can be substituted by improved information sharing.
Keywords: G21; G28; L15; 330; Creditor rights; information sharing.